Quality Assessment of Panorama Video for Videoconferencing Applications - Leorin, S.; Lucchese, L.; Cutler, Ross (Multimedia Signal Processing, 2005)
New video-conference devices based on omnidirectional multi-camera systems have been emerging in the last few years. These devices require innovative and automated video quality assessment in the earlier stages of their design in order to guarantee competitive product development and quality monitoring. Current quality assessment techniques are not adequate since they are mostly tailored to single video cameras. Even if these techniques are capable of assessing the quality of each video stream separately, the overall quality of a composite video stream generated with the outputs of multiple cameras stitched together presents strong deviations from the results of subjective quality tests. In this paper, we present new strategies for assessing the quality of composite video streams with specific emphasis on the following problems: noticeable calibration differences between adjacent cameras, concentration of motion in limited regions of the panoramic scene, combined vignetting problems, non-uniformity of the surfaces in the seam region between two adjacent cameras. Combining different features from high and low level vision, we evaluate the proposed perceptual quality metric using a set of customized test sequences and verify its correlation with subjective quality tests